Prevalence and incidence of adult attention deficit/hyperactivity disorder in a large managed care population. (July 2014) - Knight, Tara K.; Kawatkar, Aniket; Hodgkins, Paul; Moss, Robert; Chu, Li-Hao; Sikirica, Vanja; Erder, M. Haim; Nichol, Michael B.
Abstract Objectives: To estimate longitudinal trends in prevalence and incidence rates of adult ADHD 2006–2009. Research design and methods: Kaiser Permanente Southern California (KPSC) electronic medical records were analyzed to assess prevalence and incidence rates for adult ADHD. Trends over time were estimated and compared using three case definitions (ADHD diagnosis only [DX], ADHD DX and ≥2 FDA-approved ADHD prescriptions [DX + RX], and ADHD DX and ≥1 behavioral therapy visit [DX + BT]). Main outcome measures: Prevalence and incidence rates of adult ADHD. Results: Prevalence ranged from 151 (DX + RX) to 312 (DX) cases per 100, 000 members in 2006, increasing to 239 (DX + RX) and 415 (DX) cases in 2009. Prevalence based on DX + BT declined from 185 in 2006 to 94 cases per 100, 000 in 2009. In 2006, incidence ranged from 15 (DX + BT) to 68 (DX) cases per 100, 000 person-years. Incidence rates remained stable throughout the study period. Stratified analyses based on DX + RX revealed only slight variations by gender, but sharp differences by age, with younger adults demonstrating a higher prevalence overall as well as dramatic increases over the study period. Prevalence was highest among Caucasians, increasing substantially across all race groups over time. Limitations: A limitation of this study is that incidence rates may not be representative of new cases if diagnoses existed prior to enrollment in KPSC. Similarly, prevalence rates may be affected if patients sought care outside of the health plan. Conclusions: Adult ADHD prevalence in this managed care organization appears low, but showed increasing prevalence and incidence rates over time.